Impact of different nasal masks on CPAP therapy for obstructive sleep apnea: a randomized comparative trial. (24th February 2016) - Neuzeret, Pierre‐Charles; Morin, Laurent
Abstract: Introduction: Patient interface is important for the success of continuous positive airway pressure (CPAP), but few trials have examined the influence of mask choice on CPAP adherence. Objectives: To compare the impact of different nasal masks on CPAP in patients with newly‐diagnosed obstructive sleep apnea (OSA). Methods: OSA patients were randomized in a 2:3 ratio to receive CPAP via different first‐line nasal masks: ResMed Mirage FX® (MFX) or control mask (Fisher & Paykel Zest ®, HC407 ® or Philips EasyLife ® ). Mask acceptance, CPAP compliance and Home Care Provider (HCP) interventions were compared between groups after 3 months of CPAP therapy using modified intent‐to‐treat (mITT; after exclusion of patients with mouth leaks during CPAP initiation) and on‐treatment (OT; CPAP adherent) analyses. Results: Of 285 randomized patients, 90 requiring a full‐face mask were excluded, leaving 195 and 151 in the mITT and OT analyses, respectively. Mask acceptance rate was higher in the MFX versus control group (mITT: 79% vs 68%, P  = 0.067; OT: 90% vs 76%, P  = 0.022). CPAP compliance was higher (5.9 ± 1.8 vs 5.1 ± 1.6 h/night, P  = 0.011) and nasal mask issue‐related HCP visits lower (3% vs 17%, P  = 0.006) in the MFX group. Nasal mask failures due to mask discomfort (5% vs 1%) or unintentional leakage (5% vs 0%) were higher in control vs MFX group. Mask acceptance was significantly associated with fewer mask leaks ( P  = 0.002) and higher pressure therapy ( P  = 0.042). Conclusions: This study highlights differences between nasal masks for CPAP delivery and shows that initial mask selection can influence adherence and healthcare utilization during CPAP.